Tourism Impacts in Bhedetar, Dhankuta District, Nepal - Rai, Dhyanendra B. (Tribhuvan University Journal, 2013)
This paper is an attempt to explore the tourism impacts in Bhedetar, Dhankuta, one of the unique and popular places of eastern Nepal for its pleasant weather and aesthetic natural landscape to tourists particularly from Nepal and India. Based on the data collected from the field survey, including the methods such as household questionnaire, key informants survey and participatory observation, this paper discusses the impacts of tourism based activities and enterprises in both positive and negative terms on nature, society, culture and economy of Bhedetar. At the end, it suggests the roles of local organizations, district government and national government in delivering services and infrastructure for the promotion of tourism in Bhedetar.